2016
DOI: 10.14260/jemds/2016/762
|View full text |Cite
|
Sign up to set email alerts
|

Acute Encephalitis Syndrome in Children With Special Reference to Japanese Encephalitis: A Retrospective Analysis

Abstract: BACKGROUNDThe north eastern region of India is an endemic area for viral encephalitis that clinically presents as acute encephalitis syndrome (AES). The Japanese Encephalitis (JE) is the most important causative agent of AES in this region, resulting in considerable morbidity and mortality every year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Assam reported the mortality was 20.5% among the JE positive cases in the age group less than 12 yrs. 27 Time Trend Similar time trend has been reported from other parts of the country. 28 It is evident from different studies that new mutations occurring in JE virus genome due to climatic reasons, which is resulting in the emergence of new environmentally adapted mutant/strains.…”
Section: Cfrsupporting
confidence: 81%
“…Assam reported the mortality was 20.5% among the JE positive cases in the age group less than 12 yrs. 27 Time Trend Similar time trend has been reported from other parts of the country. 28 It is evident from different studies that new mutations occurring in JE virus genome due to climatic reasons, which is resulting in the emergence of new environmentally adapted mutant/strains.…”
Section: Cfrsupporting
confidence: 81%
“…Similar results have been reported in many studies: Vasanthapuram R et al reported 16% positivity for JEV among the patients with AES, but Kaliban L et al and Gogoi A et al reported significantly higher proportion of JE positive patients among the AES cases. [ 10 11 12 ] The affected age group for both AES and JE in majority was 1-5 years, followed by 5-10 years, while the least affected age group was 0-1 year. Similar results were seen in the study conducted by Kumari R et al in Uttar Pradesh, in which 58% of AES cases were from the age group 4-6 years for AES, and 75.1% cases of JE were in the age group of 15 years or less.…”
Section: Discussionmentioning
confidence: 99%
“…But in our study, younger age of 1 m to less than 1 year was found to be associated with better prognostic outcome. 10,11 Burke et al also did not find any association between age and outcome in AES patients. 12 Among the 105 male patients, 35 expired constituting 33.3% and 41(39%) were discharged without sequelae.…”
Section: Resultsmentioning
confidence: 94%